2016
DOI: 10.3389/fpsyg.2016.00329
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval Interference in Syntactic Processing: The Case of Reflexive Binding in English

Abstract: It has been proposed that in online sentence comprehension the dependency between a reflexive pronoun such as himself/herself and its antecedent is resolved using exclusively syntactic constraints. Under this strictly syntactic search account, Principle A of the binding theory—which requires that the antecedent c-command the reflexive within the same clause that the reflexive occurs in—constrains the parser's search for an antecedent. The parser thus ignores candidate antecedents that might match agreement fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 42 publications
(126 reference statements)
5
73
0
Order By: Relevance
“…To increase the strength of the inaccessible subject, they used an object pronoun within a relative clause where the inaccessible antecedents were the subject of the clause. Patil et al (2016) found a significant main effect of interference in First Pass and in First Pass Regression Probability. There was also a main effect of match for Rereading times and Total Reading Times.…”
Section: Evidence Of the Initial Fallibility Of The Structural Constrmentioning
confidence: 82%
See 4 more Smart Citations
“…To increase the strength of the inaccessible subject, they used an object pronoun within a relative clause where the inaccessible antecedents were the subject of the clause. Patil et al (2016) found a significant main effect of interference in First Pass and in First Pass Regression Probability. There was also a main effect of match for Rereading times and Total Reading Times.…”
Section: Evidence Of the Initial Fallibility Of The Structural Constrmentioning
confidence: 82%
“…Qualitative factors are also important since structural cues are weighted more strongly in retrieval than morphological cues. Patil et al (2016) thought that reflexive binding may be a very informative phenomenon in understanding the role that grammatical and non-grammatical constraints play in memory. The structural constraints of reflexive binding are relatively clear, and this construction admits manipulations of agreement, distance, and distracting antecedent candidates.…”
Section: Evidence Of the Initial Fallibility Of The Structural Constrmentioning
confidence: 99%
See 3 more Smart Citations